Kendbona Eco-development Project - a Novel Approach to Wasteland Reclamation - Chowdhury, M. K. (Indian Forester, 1992)
Reclamation of wasteland through silviculture has been the declared policy of the country since the mid eighties. Ambitious programmes have been drawn up for afforestation of wasteland both within the demarcated forest land and outside. It is being increasingly realized that peoples' participation in such efforts is most important for such projects to succeed. However, popular involvement can only result if the people, who are essentially poor, can find some immediate and tangible benefit flowing out to them from such projects. Forestry schemes, even when based on short rotation, quick growing species, calls for a minimum gestation period of 5-7 years, which is rather too long for the rural poor to wait. It is here that experimentation in multi-tier forestry is called for, where quick-yielding cash crops like Sabai (Eulaliopsis binata), etc. can be grown as a second tier with tree crop. Where permissible, interspace between the tree crop may be utilised to raise agricultural crops that are compatible with the tree crops. Such intercrops will ensure an immediate economic return for the people participating in the afforestation and eco-development project leading to popular involvement and active participation in the effort. This paper describes the success story of a micro-level ecodevelopment project through afforestation and intercropping, with the active participation of beneficiaries, who were all women